2018
DOI: 10.15419/bmrat.v5i10.492
|View full text |Cite
|
Sign up to set email alerts
|

The effect of delivery type on neonatal blood indices in an Iranian population

Abstract: Background: Generally, there are two methods for childbirth: normal vaginal and cesarean section (C-section). Each method has advantages and complications. In this study, we investigated the effects of type of delivery on hematological parameters in healthy full-term neonates in an Iranian population, from 2016-2017. Materials: Three hundred pregnant women, along with their healthy and term babies, were studied. According to the route of delivery, the neonates were divided into two groups: vaginal (n=150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
3
3
Order By: Relevance
“…Furthermore, in the preterm newborn, kidney is immature that cannot produce sufficient amount of erythropoietin level, which results in development of anemia as compared to full-term babies [30]. Moreover, our finding anemia prevalence was lower compared to the study reported from Iran (53%) [31]. The possible reason for this discrepancy might be attributed to variation in study participants based on the mode of delivery between these studies.…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, in the preterm newborn, kidney is immature that cannot produce sufficient amount of erythropoietin level, which results in development of anemia as compared to full-term babies [30]. Moreover, our finding anemia prevalence was lower compared to the study reported from Iran (53%) [31]. The possible reason for this discrepancy might be attributed to variation in study participants based on the mode of delivery between these studies.…”
Section: Discussioncontrasting
confidence: 76%
“…In this study, 272 study participants were included, whereas a study from Addis Ababa was conducted among 89 study participants. On the contrary, the prevalence of newborn anemia in this study is lower as compared to studies done in Brazil 32.6%, 22 India 39%, 11 79.3%, 23 Iran 53%, 24 Ghana 57.3%, 25 Benin 61.1%, 26 Ethiopia 29.1%. 27 The possible difference from the Benin study might be attributed to the Benin study included newborns delivered from malaria-infected mothers only, whereas in the present study newborns delivered from malaria-free mothers were also included in the study.…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly, neonates delivered via Caesarean section in the present study were observed to be more anaemic. This was in consonance with the study in Iran [31]. Anaemia could be observed more in operative deliveries because of the possibility of accidental incision of the placenta resulting in bleeding with subsequent anaemia in the newborn.…”
Section: Discussionsupporting
confidence: 89%